2009
DOI: 10.14214/sf.186
|View full text |Cite
|
Sign up to set email alerts
|

A techno-economic evaluation of Bracke and M-planter tree planting devices

Abstract: Techno-economically reasonable mechanization of tree planting has proved to be a difficult task in the Nordic working conditions. Although planting machines and combinations of base machine and planting device have been developed since the 1970s, mechanized planting has not been cost-competitive to manual planting. The aim of this study was to find out work time distributions, productivities, costs and effects of different work difficulty factors on productivities and costs of the state-of-the-art Nordic plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
74
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(81 citation statements)
references
References 6 publications
4
74
3
Order By: Relevance
“…Cost-efficiency is hampered by low productivity, which originates from operator inexperience, among other reasons [12]. The choice of worksites also strongly influences productivity, and it has been reported that the presence of stones, slash, and stumps decreases the planting machines' productivity [13][14][15][16][17]. The size and spatial distribution of worksites also affects cost-competitiveness [18].…”
Section: Introductionmentioning
confidence: 99%
“…Cost-efficiency is hampered by low productivity, which originates from operator inexperience, among other reasons [12]. The choice of worksites also strongly influences productivity, and it has been reported that the presence of stones, slash, and stumps decreases the planting machines' productivity [13][14][15][16][17]. The size and spatial distribution of worksites also affects cost-competitiveness [18].…”
Section: Introductionmentioning
confidence: 99%
“…CSFs also include site stoniness and expertise of planting machine operator because these factors had the greatest gap between realization and importance, i.e., respondents considered them important but their performance in 2013 was poor. Site stoniness has been reported to significantly decrease the productivity of planting work whereas collecting slash has a lower effect on productivity (Rantala et al 2009;Rantala and Laine 2010). Thus, worksite selection is an important factor.…”
Section: Discussionmentioning
confidence: 99%
“…A second recommendation would be that a careful appraisal of worksite suitability for mechanized planting is important because stoniness, stumps and slash debris significantly diminish productivity (Saarinen 2006;Rantala et al 2009;Rantala and Laine 2010;Laine and Rantala 2013;Ersson 2014). Also, by avoiding small worksites and optimizing the number of and distance between machine relocations, mechanized planting can become more efficient (Rantala et al 2009;Hallongren et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations